When staged surgical treatment can solve bilateral axillary and inguinal severe hidradenitis suppurativa: Staged surgical treatment for hidradenitis - Pierazzi, Diletta Maria; Calabrese, Sarah; Pica Alfieri, Edoardo; Faini, Gianpaolo (Acta Biomedica Atenei Parmensis, 2022)
Hidradenitis suppurativa (HS) is a chronic and debilitating disease that primarily affects the axillary, inguinal and anogenital areas. The treatment requires wide surgical excision of the affected tissue with adequate free margins in order to avoid recurrence. However, axillary and inguinal regions reconstruction after HS excision still represents a big challenge; the large defect can be closed using flaps, which allows more rapid rehabilitation and minimizes the risk of later scar contracture. In this report is discussed our experience with reconstruction of severe bilateral hidradenitis lesions of the axillary and inguinal areas in a young woman. Bilateral thoracodorsal artery perforator flaps were used for the axillary reconstruction while profunda artery perforator flap and direct suture were used respectively for left and right inguinal region.